Optical anisotropy in semipolar (Al,In)GaN laser waveguides - Scheibenzuber, W.; Schwarz, U.; Veprek, R.; Witzigmann, Bernd; Hangleiter, Andreas (Physica Status Solidi (C) Current Topics in Solid State Physics, 2010)
In this work, the optical eigenmodes of a semipolar (Al,In)GaN laser diode are calculated. A full vectorial one-dimensional 4x4 transfer matrix method is used to correctly incorporate the influence of birefringence of the wurtzite crystal. Depending on the orientation of the laser waveguide relative to the c-axis, the eigenmodes show TE/TM- or extraordinary/ordinary polarization. The polarization direction of the eigenmodes is crucial for the performance of the laser, as it determines the relevant interband matrix elements for the optical gain. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA.
CRIS-Team Scopus Importer:2021-06-11
Keywords: (Al; In)GaN; Laser; Optical properties; Waveguides